Time to Care for Male Nurses: Confronting Stigma and Workforce Imbalance - Saldy Yusuf; Muhammad Arsyad Subu (Indonesian Contemporary Nursing Journal (ICON Journal), 2026)
Nursing remains predominantly female worldwide, even as the need for a diverse healthcare workforce grows. Nurses are the largest group of healthcare professionals; however, the profession faces an increasing shortage. Although nursing has expanded rapidly (Kouta & Kaite, 2011), it is often associated with traditional, female caregiving roles. In the Western world, Florence Nightingale is celebrated as a key figure in nursing (Turkowski & Turkowski, 2024), whereas Rufaidah Al-Aslamiyah is recognized in the Islamic world (Bodrick et al., 2022). Both are women, and their status as pioneers perpetuates the idea that nursing is a feminist profession. Historically, Indonesia has limited nursing education to female students, reinforcing this stigma. This perception has become a global issue (Subu et al., 2022), leading to fewer male nurses at all educational and professional levels in the field. For instance, a nursing school noted that a male student withdrew because he was the only male participant. Research indicated that male nurses often feel isolated or marginalized (Yip et al. 2021).